Corpus-Driven Visualization of Textual Worlds - Kofoed, Jens Bruun (HIPHIL Novum, 2017)
EuroPLOT resources [http://resources.3bmoodle.dk] is a unique collection of close to 5000 images of people, places and customs related to the world of the Bible. Pictures selected for the database are high resolution images of 10 megapixels or more (except for images of historical interest). All pictures are tagged with information on the picture’s motif, relevant historical period(s), the name of the photographer, the date when the picture was taken, and Biblical references. The core vision is to use historical-archaeological pictures from primarily Israel-Palestine, but also the broader Biblical scene (Turkey, Lebanon, Syria, Jordan and Egypt) for visualization of textual worlds. The database is constructed to illustrate how a corpus-driven persuasive technology is able to make learning more effective and efficient through scaffolding. The database is integrated with the teaching tool Bible Online Learner, which is a tutor for the study of Hebrew and Greek based on the original Biblical texts, and relevant resources in the database are displayed as links in the Biblical text. The Flood account in Genesis 6-9 will be used as a case to demonstrate the potential of the database. The programmer of Bible Online Learner, Claus Tøndering will develop the automated search learning objects. The resource database will be enhanced with a mechanism that allows a resource (that is, a picture, a sound, a video, or a piece of text) to be associated with an entry in a Hebrew or Greek dictionary. Bible Online Learner will then be able to provide a link to that resource when the associated word occurs in the biblical text. We will furthermore for the project explore to what extent we can use internationally established standards for reference to location on the internet, i.e. a “Uniform Resource Name” and explore to what extent this will enable Bible OL to associate our dictionary entries with other digital library formats (e.g., Bible Odyssey, Wikimedia Commons, etc.) for canonical citation. The high resolution resources are made freely available for non-commercial uses, and therefore an important resource for Majority World researchers, teachers and learners. All resources will be tested in the classrooms in Copenhagen, Oslo, Mongolia, Madagascar, Kenya and elsewhere over the next years.